Nanocellulose significantly reduces number of anesthetics, hospital days, and in-patient dressing changes compared to PU-Foam Dressing: a prospective cohort study in children - Renkert-Baudis, Miriam; Günter, Florentine; Mohr, Christoph; Maurer, Kristina; Klinke Petrowsky, Michaela; Boettcher, Michael; Elrod, Julia (Burns, 2024)
Background - Pediatric thermal injuries can have profound physical and psychological effects. Long-term care, including wound dressing selection, significantly impacts outcomes. This study compared treatment related variables and long-term results of bacterial nanocellulose (BNC) and polyurethane foam (PU-foam) dressings in pediatric burn care. - Methods - A prospective cohort study comparing BNC (2018-2020) and PU-foam (2016-2018) in pediatric burn patients. Data included demographics, wound characteristics, infection rates, treatment duration, anesthesia procedures, dressing changes, scar assessments (POSAS, VSS), colorimeter measurements, and quality of life (CDLQI). Regression analyses were performed to correct for differences in burn depth. - Results - After correction for burn depth, BNC showed a shorter hospital stay duration (p = 0.007), a lower number of procedures under general anesthesia (p<0.0001) and a reduced number of inpatient dressing changes (p = 0.006), compared to PU-foam, whereas wound infection rates did not differ between the treatment groups (p = 0.169). Scar outcomes (POSAS, VSS, colorimeter measurements) and quality of life (CDLQI) were comparable for both treatments. - Discussion - BNC dressing benefits include significantly fewer anesthesia procedures, a reduced number of inpatient dressing changes and a shorter hospital stays, supporting the use of BNC dressing. Long-term scar outcomes with BNC are comparable to established dressings like PU-foam. Further randomized trials are necessary to confirm these findings.
Online verfügbar: 9. Juli 2024, Artikelversion: 5. Dezember 2024
Gesehen am 17.04.2025